Synthesis, structural and optical characterization of ZnO crystals grown in the presence of silver - Rodrigues, J.
Zinc oxide microcrystals grown at atmospheric pressure by the laser assisted flow deposition method were characterized by morphological, structural and optical techniques. A set of samples with 0, 0.8, 2.0, 3.0 and 5.0 mol% nominal AgNO3 content were studied in order to analyse the influence of silver amount on the near band edge recombination. A detailed study of the samples' photoluminescence evidence that at room temperature the free exciton recombination occurs at ~3.334 eV for crystals grown in the presence of silver instead of the broad peak observed at ~3.28 eV for the undoped ones